KONSEP MERDEKA BELAJAR PENDIDIKAN INDONESIA DALAM PERSPEKTIF FILSAFAT PROGRESIVISME - Faiz, Aiman; Kurniawaty, Imas (Universitas Islam Balitar, 2020)
The purpose of this study is to describe the phenomena associated with the needs of Indonesian education in facing the challenges of the 21st century. The main thing in this article is the concept of John Dewey's philosophy of progressivism which is integrated with the concept of Indonesian education. In this study using library research to explore relevant concepts. The research approach used is descriptive qualitative method, the aim is to observe the phenomenon of education in Indonesia. The results showed that the Indonesian education system currently conceptualized by the Minister of Education and Culture (Nadiem Makarim) refers to John Dewey's concept of philosophical thought progressivism. The main thing in this concept emphasizes that humans must keep abreast of the times as well as the education system. This is in line with the concept of live long education. Another aspect is the importance of skill development and character performance. Character development is important to balance intelligence and character abilities. Besides character, education must be able to develop critical and creative thinking, so that it can discover new things and be able to produce graduates with an entrepreneurial spirit who is able to manage the country and all its potential. With this research being the first step for researchers and practitioners in the field of education to develop the concept of Indonesian education based on educational concepts that are in accordance with the conditions of the times and the current challenges.